2016
DOI: 10.7567/jjap.56.03bb01
|View full text |Cite
|
Sign up to set email alerts
|

Self-aligned metal double-gate junctionless p-channel low-temperature polycrystalline-germanium thin-film transistor with thin germanium film on glass substrate

Abstract: Low-temperature (LT) polycrystalline-germanium (poly-Ge) thin-film transistors (TFTs) are viable contenders for use in the backplanes of flat-panel displays and in systems-on-glass because of their superior electrical properties compared with silicon and oxide semiconductors. However, LT poly-Ge shows strong p-type characteristics. Therefore, it is not easy to reduce the leakage current using a single-gate structure such as a top-gate or bottom-gate structure. In this study, self-aligned planar metal double-ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…Finally, annealing at 300 °C was performed to facilitate the formation of metal-SD by atomic exchange between Al and Ge, which is named as aluminum-induced lateral metallization SD (Al-LM-SD). This technique was first reported by A. H., and we used it to form low parasitic resistance metallic SD [18]. Figure 2 shows the top-view photograph of the fabricated TFT with a gate length of 20 μm.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Finally, annealing at 300 °C was performed to facilitate the formation of metal-SD by atomic exchange between Al and Ge, which is named as aluminum-induced lateral metallization SD (Al-LM-SD). This technique was first reported by A. H., and we used it to form low parasitic resistance metallic SD [18]. Figure 2 shows the top-view photograph of the fabricated TFT with a gate length of 20 μm.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…TFT performance Figure 6 shows the fabricated TFTs, which were annealed for 60 min at 300 °C, the final annealing to form Al-LM-SD. Our previous study demonstrated that the gray region in the SD comprises metallic Al, which is grown by a lateral atomic exchange process between the electrode Al and poly-Ge film [5]. This leads to low parasitic resistance of the SD region and high on-current by a simple and inexpensive process at a low temperature of 300 °C.…”
Section: P-228 / H Utsumimentioning
confidence: 99%
“…In our previous research, we reported a self-aligned planar metal double-gate (MeDG) JL p-ch LT solid-phase crystallization (SPC) poly-Ge TFT on a glass substrate, where in a 15-nm-thick SPC poly-Ge film and aluminum (Al) induced lateral metallization (LM) source-drain (Al-LM-SD) were used to reduce the offcurrent and SD resistance [5]. A self-alignment process was used to align the top and bottom metal gates, in which the bottom metal gate was used as a photomask.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations